Galkin's lower bound conjecture holds for the Grassmannian. Issue 2 (1st February 2020) - Evans, La'Tier; Schneider, Lisa; Shifler, Ryan M.; Short, Laura; Warman, Stephanie
Abstract: Let Gr ( k, n ) be the Grassmannian. The quantum multiplication by the first Chern class c 1 ( Gr ( k, n ) ) induces an endomorphism c ̂ 1 of the finite-dimensional vector space QH * ( Gr ( k, n ) ) | q = 1 specialized at q  = 1. Our main result is a case that a conjecture by Galkin holds. It states that the largest real eigenvalue of c ̂ 1 is greater than or equal to dim  Gr ( k, n ) +1 with equality if and only if Gr ( k, n ) = P n − 1 .